2020
DOI: 10.1177/1460458220921707
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of clinician and patient views regarding the use of a preconception care app for women with diabetes

Abstract: Women with diabetes are at increased risk of adverse maternal and foetal outcomes. Preconception care can minimise risk of complications and improve outcomes, but current provision is inadequate. Electronic health technology, particularly apps, could improve preconception care provision but research is lacking in this area. The aim of this article is to explore the views and experiences of clinicians and women with diabetes regarding the use of a mobile app for preconception care. An exploratory study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…This study also found health care providers' lack of knowledge about preconception care as barriers to its uptake. This finding was supported by studies conducted in the United Kingdom, Netherland, Ireland, Malaysia, and Iran [26,[31][32][33]40]. The current and previous studies showed that some health care providers were not familiar with this issue.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This study also found health care providers' lack of knowledge about preconception care as barriers to its uptake. This finding was supported by studies conducted in the United Kingdom, Netherland, Ireland, Malaysia, and Iran [26,[31][32][33]40]. The current and previous studies showed that some health care providers were not familiar with this issue.…”
Section: Discussionsupporting
confidence: 76%
“…The current study as well as earlier studies [ 26 , 29 , 33 , 36 , 37 ], recognized unplanned pregnancy as an important deterrent to the uptake of preconception care. These findings implicated unplanned pregnancy remains affecting maternal and child health.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Consequently, insufficient PCC coverage and subsequent high rates of adverse maternal/fetal outcomes have remained a persistent public health challenge [9,[38][39][40]. There is therefore a need to leverage smartphone use in the delivery of PCC to women with DM [9,13,41].…”
Section: Introductionmentioning
confidence: 99%